On Some Integral Inequalities in Quantum Calculus. (6th October 2020) - Jleli, Mohamed; Samet, Bessem
Abstract : The objective of this paper is to establish q -analogue of some well-known inequalities in analysis, namely, Poincaré-type inequalities, Sobolev-type inequalities, and Lyapunov-type inequalities. Our obtained results may serve as a useful source of inspiration for future works in quantum calculus.